2015
DOI: 10.1108/scm-06-2015-0217
|View full text |Cite
|
Sign up to set email alerts
|

A decade of supply chain collaboration and directions for future research

Abstract: Purpose – This paper aims to conduct a systematic review of the literature on supply chain collaboration published over a 10-year period from 2005 to 2014. It explores the nature and extent of research undertaken to identify key themes emerging in the field and gaps that need to be addressed. Design/methodology/approach – The authors review a sample of 207 articles from 69 journals, after using an iterative cycle of defining appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(301 citation statements)
references
References 152 publications
3
257
1
10
Order By: Relevance
“…Our research contributes to the work by Trkman et al (2015) on the intra-and interorganisational capabilities, and the extension of the body of knowledge on SCC argued by Soosay and Hyland (2015). The results show both mutual benefits in the form of collaborative advantage, and individual benefits in terms of organisational performance.…”
Section: Implications For Theorymentioning
confidence: 57%
See 2 more Smart Citations
“…Our research contributes to the work by Trkman et al (2015) on the intra-and interorganisational capabilities, and the extension of the body of knowledge on SCC argued by Soosay and Hyland (2015). The results show both mutual benefits in the form of collaborative advantage, and individual benefits in terms of organisational performance.…”
Section: Implications For Theorymentioning
confidence: 57%
“…Prior research has identified SCC in various ways, with common sentiments focusing on the relationship (Vereecke and Muylle, 2006;Cao and Zhang, 2011), the process (Simatupang and Sridharan, 2008;Fawcett et al, 2008, Cao andZhang, 2011), and gaining mutual benefits from collaborating with SC partners (Fawcett et al, 2015;Soosay and Hyland, 2015). SCC aims at mutual benefits and profit maximisation for the involved SC members through a well-coordinated planning and delivery of offerings (Simatupang and Sridharan, 2008;Cao and Zhang, 2011).…”
Section: Supply Chain Collaboration and Its Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, a systematic literature review in terms of the availability of suitable methods points towards the following claims: research claiming for the need for mixed methods research in RGSCM (Dubey et al, 2015;Faisal, 2016); research claiming for the need of quantitative based modelling & decision support in RGSCM (Heckmann, Comes & Nickel, 2015;Qazi et al, 2015;Taticchi et al, 2015); research claiming for the need of mixed methods when analyzing systems that include environment, society and cross-system innovation/ practice diffusion (Smith & Rupp, 2015;Soosay & Hyland, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Collaboration is possible when two or more actors share their efforts to achieve a common objective and in transportation it involves a physical exchange of shipments between collaborating partners, who share material and immaterial resources in the form of logistics facilities, vehicles, information as well as planning and optimisation methods (17). Unlike vertical collaboration, which involves partners positioned at different levels of a supply chain (18,19), horizontal collaboration aims to identify and achieve win-win situations (e.g. improved optimisation, loaded capacity and asset utilisation (20,21)) between organisations that may or may not be competitors operating at the same level of a supply chain.…”
Section: Approaches To Collaborationmentioning
confidence: 99%